An open trial of Acceptance-based Separated Family Treatment (ASFT) for adolescents with anorexia nervosa. (June 2015) - Timko, C. Alix; Zucker, Nancy L.; Herbert, James D.; Rodriguez, Daniel; Merwin, Rhonda M.
Abstract: Family based-treatments have the most empirical support in the treatment of adolescent anorexia nervosa; yet, a significant percentage of adolescents and their families do not respond to manualized family based treatment (FBT). The aim of this open trial was to conduct a preliminary evaluation of an innovative family-based approach to the treatment of anorexia: Acceptance-based Separated Family Treatment (ASFT). Treatment was grounded in Acceptance and Commitment Therapy (ACT), delivered in a separated format, and included an ACT-informed skills program. Adolescents (ages 12–18) with anorexia or sub-threshold anorexia and their families received 20 treatment sessions over 24 weeks. Outcome indices included eating disorder symptomatology reported by the parent and adolescent, percentage of expected body weight achieved, and changes in psychological acceptance/avoidance. Half of the adolescents (48.0%) met criteria for full remission at the end of treatment, 29.8% met criteria for partial remission, and 21.3% did not improve. Overall, adolescents had a significant reduction in eating disorder symptoms and reached expected body weight. Treatment resulted in changes in psychological acceptance in the expected direction for both parents and adolescents. This open trial provides preliminary evidence for the feasibility, acceptability, and efficacy of ASFT for adolescents with anorexia. Directions for future research are discussed. Highlights: We developed and an acceptance-based family treatment for adolescent anorexia. Full remission in 49% of cases and partial remission in 30% of cases. A significant reduction in self-reported and observed eating disorder behavior. Acceptance increased and avoidance decreased over the course of treatment. Paternal belief in treatment outcome was a significant predictor of outcome.